Analisis Faktor Pendorong Urbanisas Menggunakan Sem-PLS di Kabupaten Purwakarta - Raihan Atallah Al-Wahid; Ade Adrianto; Fikri Ilyasa (Jurnal Noken: Ilmu-Ilmu Sosial, 2026)
Urbanization is a demographic phenomenon influenced by various factors and has significant impacts on the social, economic, and environmental conditions of a region. Purwakarta Regency has experienced dynamic urbanization alongside industrial development and improved regional connectivity. This study aims to analyze the effects of economic, socio-demographic, and infrastructure factors on the rate of urbanization and the impacts of urbanization in Purwakarta Regency. The study employed a quantitative approach using multivariate analysis through Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 81 respondents using a questionnaire consisting of 50 items. The results indicate that economic factors have a significant positive effect on the urbanization rate (β = 0.609; p < 0.001) and the impacts of urbanization (β = 0.465; p < 0.001), whereas socio-demographic factors significantly affect only the urbanization rate (β = 0.203; p = 0.020) and have no significant direct effect on the impacts of urbanization (β = 0.197; p = 0.143). Infrastructure serves as a supporting factor that strengthens the urbanization process by improving regional accessibility. The study concludes that urbanization in Purwakarta Regency is a multifactorial phenomenon, with economic factors serving as the primary determinant.